Enhancing Students' Reading Comprehension Using Let’s Read Application In Visualization Strategy - Awanda Mella Stevani; Ririn Ambarini; Ajeng Setyorini (Lembaga Pengembangan Kinerja Dosen, 2023)
The primary goal of this study was to measure the effectiveness of Let's Read app in visualization strategy in improving students' reading ability. Let’s Read is an application that contains many stories with audio and is equipped with visual pictures that can help students learn to read. This study uses a quantitative and pre-experimental design to test. The pre-experimental used 2 tests, the pre-test at the beginning and the post-test after treatment. The sample in this research consisted of 36 tenth-grade students. The results confirmed that the post-test scores increased and exceeded the pre-test values. Furthermore, at a significant level of 0.05%, the t-score is calculated to be smaller than t-table. From this analysis, the Alternative Hypothesis (Ha) was accepted, while the Null Hypothesis (Ho) was rejected. Based on the facts through the results of data analysis, using Let's Read app in visualization strategy is proven to help in enhance students' reading comprehension. As a result, it is recommended that educators and students take advantage of this application to enhance reading comprehension.